2014
DOI: 10.1590/0001-3765201420130180
|View full text |Cite
|
Sign up to set email alerts
|

Bark Harvesting Systems of Drimys brasiliensis Miers in the Brazilian Atlantic Rainforest

Abstract: Drimys brasiliensis Miers, locally known as cataia or casca-de-anta, is a native tree species of the Atlantic Rainforest. Its bark is harvested from natural populations. This study examined the recovery capacity of the bark of D. brasiliensis under different bark harvesting methods, as well as the influence of these approaches on its population dynamics and reproductive biology. While none of these treatments resulted in changes in phenological behavior or the rate of increase of diameter at breast height and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
2
11
2
Order By: Relevance
“…Bark is one of the most important plant parts used as raw material in traditional medicine worldwide, as well as in urbanindustrial societies (Cunningham, 2014a; Senkoro et al, 2014; Mariot et al, 2014. Bark is also the most commonly extracted plant parts for biological activity tests in laboratories (Cunningham, 2014a; Kemppainen et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Bark is one of the most important plant parts used as raw material in traditional medicine worldwide, as well as in urbanindustrial societies (Cunningham, 2014a; Senkoro et al, 2014; Mariot et al, 2014. Bark is also the most commonly extracted plant parts for biological activity tests in laboratories (Cunningham, 2014a; Kemppainen et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Cunningham and Mbenkum (1993) indicated that Prunus africana in Cameroon can achieved complete bark re-growth after ring barking. Bark regrowth from the edges recorded for Prunus africana trees was also found for Drimys brasiliensis (Mariot et al, 2014) and Himatanthus drasticus (Baldauf and dos Santos, 2014). However, over the two-year follow-up period, some trees are able to close the wound completely, suggesting a recovery time of about two years.…”
Section: Bark Recovery Rates After Debarking Influence Of Altitude mentioning
confidence: 68%
“…Knowledge of reproductive biology in the context of floral morphology and interaction with biotic vectors is important for predicting species survivability (Faegri and Van der Pijl 1979, Rodríguez-Pérez 2005, understanding gene flow patterns and genetic differentiation of populations (O'Malley et al 1988, Bawa 1992) and supporting conservation and sustainable management efforts (Mariot et al 2014). Nevertheless, most V. curassavica studies have reported on its phytochemistry and pharmacology (Carvalho Jr. et al 2004, Fernandes et al 2007, Passos et al 2007, while neglecting important questions of autoecology (Opler et al 1975, Brandão et al 2015.…”
Section: Varronia Curassavica Jacq (Boraginaceae) Is a Characteristimentioning
confidence: 99%